La representación del poder en las obras La casa de los espíritus y Eva Luna de Isabel Allende - Villagómez Zúñiga, Nicole Germania (2024)
The present investigation characterizes the representation of power in the novels. The house of the spirits and Eva Luna, considering the context of the time in Chile when the military coup occurred. The research corresponds to a qualitative approach, a nonexperimental study, and the typologies: exploratory, descriptive, bibliographic documentary and transversal; Likewise, hermeneutic method and techniques based on observation and underlining; The instrument is an analysis matrix in which Greimas' theory is used to identify the feminine and masculine power of the two works. It is concluded that the woman, in these novels, undoubtedly came to prevail in her power; while one fights against a patriarchal system to obtain independence and personal freedom. Keywords: Isabel Allende, feminism, power, literature